2018
DOI: 10.1177/0009922818803398
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perception and Participation in Genetic Testing Among Children With Autism Spectrum Disorders

Abstract: The purpose of this study was to determine the factors associated with genetic testing in children with autism spectrum disorders (ASDs) and understand parental involvement in the decision to test using survey data of parents of children with ASD. Evaluation by a geneticist was associated with genetic testing by more than 39 times compared to evaluation by a nongeneticist (95% CI = 9.15-168.81). Those offered testing by the physicians were more than 6 times more likely to be tested than those not offered testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
5
17
0
Order By: Relevance
“…It is worth noting that although factor 2 (perceived ASD genetic testing as unnecessary) of the Perceived Barriers in Pursuing Genetic Testing for Children with ASD Scale was dropped from CFA analysis due to only two items being identified through EFA analysis, it is still an important sub-domain. This is consistent with previous studies [53][54][55][56] that showed that parents of children with ASD were concerned about the necessity, practical benefits, and usefulness of genetic testing for children with ASD. Future research should develop additional items to measure this dimension, which can assist in better understanding parental concern regarding the necessity of genetic testing for their children with ASD.…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that although factor 2 (perceived ASD genetic testing as unnecessary) of the Perceived Barriers in Pursuing Genetic Testing for Children with ASD Scale was dropped from CFA analysis due to only two items being identified through EFA analysis, it is still an important sub-domain. This is consistent with previous studies [53][54][55][56] that showed that parents of children with ASD were concerned about the necessity, practical benefits, and usefulness of genetic testing for children with ASD. Future research should develop additional items to measure this dimension, which can assist in better understanding parental concern regarding the necessity of genetic testing for their children with ASD.…”
Section: Discussionsupporting
confidence: 91%
“…Many of our participants had moderate to high annual household incomes and high educational attainment; thus, our findings might be more representative of parents with a high socioeconomic status. Moreover, in line with other ASD research (Harrington et al., 2018; Narcisa et al., 2013), our sample was primarily comprised of mothers who were White. Future studies should consider targeting the recruitment of fathers and racial/ethnic minority parents to broaden the understanding of parental intention to pursue genetic testing for their children with ASD.…”
Section: Discussionmentioning
confidence: 90%
“…Although the AAP (Hyman et al., 2020; Moeschler & Shevell, 2014), the ACMG (Schaefer & Mendelsohn, 2013), and AAN (Michelson et al., 2011) recommend genetic testing for children diagnosed with ASD, the uptake rate is low in the United States (Cuccaro et al., 2014; Harrington et al., 2018; Kiely et al., 2016; Narcisa et al., 2013; Wydeven et al., 2012; Zebolsky et al., 2020; Zhao et al., 2019). To the best of our knowledge, this is the first study that examined a large sample of parents of children with ASD regarding their intention to pursue genetic testing for their children with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 105 were excluded based on lack of empirical results, or study designs that focused on hypothetical response to genetic testing, pre-test perceptions of genetic testing, and/or non-parent/caregiver reported outcomes. Thirty-three [ 15 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] met all inclusion criteria Figure 1 . All full texts were reviewed for inclusion by two independent reviewers, with an inter-rater agreement of 83.4%.…”
Section: Resultsmentioning
confidence: 99%